Assessing the health and nutrition risks of smallholder poultry production in Burkina Faso: Insights from formative research - Gelli, Aulo; Headey, Derek D.; Ngure, Francis; Becquey, Elodie; Ganaba, Rasmané; Huybregts, Lieven; Pedehombga, Abdoulaye; Sanou, Armande; Traore, Abdoulaye; Zongo, Florence; Zongrone, Amanda (International Food Policy Research Institute, 2017)
The Soutenir l’Exploitation Familiale pour Lancer l’Élevage des Volailles et Valoriser l’Économie Rurale (SELEVER) study is designed to evaluate the impact of an integrated agriculture-nutrition intervention package (including poultry value chain development; women’s empowerment activities; and a behavior change communications strategy to promote improved diets and feeding, care, and hygiene practices) on the diets, health, and nutritional status of women and children in Burkina Faso. The aim of the formative research was to assess the need for an intensive water, sanitation, and hygiene (WASH) and poultry-related hygiene component that could be rolled out alongside the SELEVER intervention in the context of the cluster randomized controlled trial. This paper is based on an observational mixed-methods study that included a literature review, pathways analysis, and primary and secondary data analysis. A theory-based framework was developed to map the different pathways linking WASH, animal husbandry practices, and child nutrition and development outcomes. This framework was used to critically review the literature on each of the pathways involved. Hygiene-related programmatic materials from the SELEVER intervention were also reviewed. Secondary data were analyzed on livestock rearing, WASH practices, and exposure to human and livestock feces. Primary research included data collection from three selected villages where SELEVER activities were being piloted, including direct observations of 20 caregiver-child pairs, in-depth interviews, and focus groups. The literature review suggested that WASH interventions have substantial potential for improving child nutrition, though the evidence on their effectiveness is far from definitive. The secondary data analysis confirmed that exposure to poultry and poultry feces is extremely widespread in Burkina Faso. Fully 80 percent of rural households owned poultry, and most poultry could roam freely throughout the compound. Visible animal feces were reported in 84 percent of compounds in both the CHANGE and PROMIS surveys. Moreover, WASH practices and general hygiene were very low: toilet ownership was extremely low (22 percent nationally), water supply was a major constraint, and handwashing with soap was very rare (in the CHANGE survey, only 2 percent of households reported having soap for handwashing). The primary data confirmed the poor state of WASH, extreme exposure to poultry and poultry feces, and poor knowledge of the risks associated with children’s exposure to animal feces. The hygiene-related content of the SELEVER intervention focuses primarily on the promotion of practical measures to improve WASH-related practices at the household level, including food preparation, water and sanitation, and waste management, with some messaging on the risks of exposure to animal feces. Emerging evidence suggests that exposure to animal feces is an important health risk for young children. However, the question of how to best mitigate this risk programmatically is still unclear. In rural Burkina Faso, the general WASH environment appears severely constrained, and free-scavenging poultry production systems are ubiquitous. These findings suggest the opportunity to develop a community-oriented behavioral change intervention that emphasizes, rather than isolates, the importance of reducing children’s exposure to poultry feces. In the context of SELEVER, this intervention would aim to increase production and consumption of poultry products while concomitantly reducing children’s exposure to poultry feces. Scaling up an intensive WASH package alongside the standard SELEVER intervention in the context of the randomized trial would provide rigorous, policy-relevant evidence in this emerging field.